The Japanese Fighters Are More Skillful than their Chinese Counterparts, or when the Context is more important than the Text - Carlos Gutiérrez García; Mikel Pérez Gutiérrez; William Acevedo; Mei Cheung (Universidad de León, 2012)
The present study proposes a reflection on different elements (political, economic, military, social, cultural...) that condition the perception, introduction and acceptance of the martial arts in other cultures. Particularly several Chinese and Japanese martial arts articles that were published in different Spanish illustrated magazines (1899-early 20th century) are analyzed. Then we point out differences between the international success of Japan and its jujutsu, when compared to the difficulties that China faced at that time and the lack of representation of its martial practices in such international context.